Capital Structure and Firm Performance: Moderating Effect of Economic Conditions, Monetary Policy, and Stock Market Volatility - Jerry Arickson, Anak Kuta (UNIMAS Institutional Repository, 2025)
The relationship between capital structure and firm performance has received considerable attention, particularly in emerging markets like Malaysia. However, most existing studies either rely on outdated data, focus on specific industries, or overlook the influence of macroeconomic conditions. This study addresses these limitations by incorporating Gross Domestic Product (GDP) growth, the Overnight Policy Rate (OPR), and stock market volatility (VOL) as moderating variables to assess their role in the capital structure–performance relationship. Using data from 719 non-financial firms listed on Bursa Malaysia from 2012 to 2022, this study applies both static and dynamic panel regression techniques. Firm performance is measured using Return on Assets (ROA), while debt is assessed through total, long-term, and short-term debt ratios to assets. The two-step system Generalized Method of Moments (sys-GMM) model is employed to address statistical issues including multicollinearity, heteroscedasticity, autocorrelation, endogeneity, and dynamic panel bias. Results reveal a significant negative relationship between debt levels and firm performance, supporting the trade-off theory. However, GDP, OPR, and VOL do not significantly moderate this relationship, suggesting that internal firm factors may exert a greater influence than macroeconomic conditions. This finding has several implications. For managers, Managers must practice careful debt management in uncertain times. Policymakers should prioritize strengthening firm resilience over relying only on macro tools. Investors can expect more stable returns from less-leveraged firms, making capital structure a key factor in investment decisions.